Biopedagogy: a reflexive point of view on learning processes (2018)
This article aims to promote the reflection on biopedagogy as a strategy for bringing visibility to the new educational realities, which are the result of different social events. The document also seeks to facilitate progress towards the third culture and towards a humanizing episteme that links knowledge to life through the perception of living beings, in other words; an environment in which it is possible to feel, to communicate, to reason, and to build a world open to everyone. The challenge of biopedagogy is to attain complex, holistic, legitimate, and self-organized learning processes through the biology of love and tenderness. This can be achieved if communication, language, and dialogue encourage the genesis of new knowledge in the individual, respond to the changing understanding of reality, and deepen the way we relate to the planet. It is our hope that human beings develop a language of self-organization, uncertainty, and risk, as well as an ability to solve situations through alternative paths based on a universe of biolearning and pedagogies that could become the emergent paradigm.